Cinderella pneumatology as an intercultural discussion: personal, church, and theological experience sequence - Christar Arstilo Rumbay (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2022)
Pneumatology shares rich discussion to theology and its brances knowledge. Indeed, intercultural discussion to the account receives attention but has no solid ground, where I borrow Moltmann??" term, pneumatology as cinderalla theology that frequently left behind. Question on why intercultural discussion to pneumatology is one the forgotten question that need more clarification. Futher, its relation to Indonesian context provokes curiosity to the tension. By using qualitative-analysis method, this research attempts to gain knowledge concerning why pneumatological-intercultural discussion. In sum, personal, church, and theological experience encourage pneumatology to open access for intercultural discussion, specifically speaking, in relation to Indonesian context.